As representações da pobreza sob a ótica dos pobres do Programa Bolsa Família - Pereira, Maria de Fátima (2007)
The present research has as objective the study of the poor considered representations of the poverty for inserted in the Program the Stock market Family. The focus of the work is to in the representations that the “poor person”, from its social experiences, makes of its condition of poverty, in view of the context of social transformations that, each time more, has taken thousand of individuals to “the social rubbish” condition. Ahead of this reality, the condition of “poor person” if configures in a recognized and socially incarnate condition in some representations related to the “poor being”. Such questions are the conducting wire of this research, in had as well as instigated them to the forms of representations of the poverty, as they reflect in the experiences of the “poor person”, in the way as such poor persons if they present to a come back program the poor persons, in the way to interact at last with the diverse situations and in the spaces for busy them from the social place that the society of the capital them reserve.